THE PERCEIVED ROLES OF E-LEARNING IN TRAINING SALES EMPLOYEES IN THE SOUTH AFRICAN AUTOMOTIVE INDUSTRY - Kelly, Alasdair (My University, 2013)
The study of human capital and the economy dates back to mid-1950’s with the neo-Classical Growth Theory (Solow, 1956) which indicated the important role that technology and human capital play in progressing an economy and hence, a company which operates inside that economy. Therefore, just as human capital development is important in economic growth; training and development needs are an important focus because it directly affects the growth and improvement of the organisation by empowering employees to become more effective and efficient in their jobs. Technological progress in the training dimension has seen a significant increase in the use of alternative mediums to transfer knowledge. One prominent development in this area has been the rise of E-Learning. This term is not restricted to the use of desktop computers but also includes alternative mediums of… such as video conferencing and personal computer devices. The perception of employees with regards to the role that E-Learning contributes towards their development provides a useful insight into the effectiveness and value of this type of leaner-centred teaching. Fifteen semi-structured interviews with sales employees, sales managers and senior managers from a variety of Toyota dealerships were conducted. The responses indicated that the use of E-Learning was effective for all respondents. However, perspectives differed slightly between those of employees and managers. From an employee perspective the results of this research identified that the perceived role of E-Learning in training sales employees was that it contributed to increasing the knowledge and skills of employees. Although, from a managerial point of view, the role was identified as time and cost saving. When analysing the combination of results the conclusion was that E-Learning did indeed improve the knowledge and skills of employees. Therefore this result can be linked to one of the identified roles of E-Learning.
MBA thesis
Keywords: e-Learning; Education and training; Training of employees; Electronic education